Архів академіка А.М. Гродзінського - Kvasha, V.V. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2001)
The exciting diary notes of Academician A.M. Grodzsnsky, famous scientist-phytobiologist, organizer of science and public figure which he made in his youth, are published for the first time. The events of his childhood – dramatic episodes of the beginning of the Great Patriotic war and evacuation of teachers’ families of the agricultural Institute in Belaya Tserkov are reflected in the notes. The diary notes are completed by some recollections of the scientist’s mother – Vira Pylypivna Grodzinska, which are the evidence of observation, intellectual curiosity, industry and other features of her son’s character.